PENGARUH KARAKTERISTIK DEWAN TERHADAP PENGUNGKAPAN RISIKO DENGAN KEPEMILIKAN KELUARGA SEBAGAI VARIABEL MODERASI - Jae Mekar Riska Yuniar; Muchamad Syafruddin (Diponegoro Journal of Accounting, 2022)
This study aims to analyze the effect of board characteristics on risk disclosure by using family ownership as a moderating variable. This study uses independent variables (board size, frequency of board meetings, and board expertise), dependent variable (risk disclosure), and moderating variable (family ownership).The population in this study are all non-financial companies listed on the Indonesia Stock Exchange in 2017-2020. The sampling method used purposive sampling. Samples were obtained as many as 156 companies with a period of 4 years. Data were analyzed by multiple regression analysis method.The results showed that board size, frequency of board meetings, and board expertise had a significant positive effect on risk disclosure. The moderating variable of family ownership has a moderating role in the relationship between board size on risk disclosure. However, the moderating variable of family ownership shows no moderating role on the relationship between the frequency of board meetings and the expertise of the board on risk disclosure.